Resultant Deformation of Sediments from Possible Seismic Events in the Pampa de Tepuel Formation during the Carboniferous (Patagonia, Argentina) - McNall, N. B. (2018)
Deformation and deposition of sedimentary materials resulting from seismicity remain poorly understood despite their importance in identifying areas and times of intense tectonic activity in and adjacent to sedimentary basins. Such strata are often misidentified as the result of rapid deposition, and in a polar environment, could be misidentified as a result of glacial tectonism. Therefore, identification of deformational structures is essential in making accurate determinations of seismic events. Direct objectives of this study are to continue determining macroscopic deformation features characteristics that resulted from earthquake induced liquefaction of sedimentary deposits, thus furthering our understanding of when and where seismic activity occurred in deep time. The Pampa de Tepuel Formation in Tepuel-Genoa Basin (Patagonia, Argentina), of Carboniferous age strata, is composed of fine-grained shelf sandstone and mudrocks deposited on a marine shelf-slope edge. The section contains mass transport deposits and an abundance of m-scale deformation structures. The mass transport deposits include slides and slumps of shelf sands that slid down the basin slope away from the shelf edge. Contained within these deposits, and within deposits on the shelf, are abundant load structures and dewatering features (pipes, sheets, and diapirs) of various sizes which are suggestive of liquefaction and deformation of sediment before lithification, and before they slid down the slope away from the shelf edge. Comparisons of these features to strata from Mississippian age deposits in Kentucky, U.S.A. that were previously interpreted as seismites suggest that seismic activity may have influenced the sedimentation in the Pampa de Tepuel Formation.